2022
DOI: 10.1002/aenm.202200453
|View full text |Cite
|
Sign up to set email alerts
|

Semitransparent Organic Solar Cells with Efficiency Surpassing 15%

Abstract: counterparts and is very attractive for developing semitransparent organic solar cells (ST-OSCs), which have great potential application in building integrated photovoltaic, agricultural greenhouse, car window, and so on. [5,6] Different from opaque device that is concerned mostly with power conversion efficiency (PCE), ST-OSCs also value the transparency in the visible region and adopt average visible transmittance (AVT) to assess their see-through function. [7] However, there is a trade-off relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 80 publications
1
75
0
Order By: Relevance
“…To further illustrate the impact of introducing the BDD unit on charge recombination, transient photovoltage (TPV) measurements were conducted. 65 As shown in Fig. S23 (ESI†), the TPV decay dynamics of the blend films can be used to extract the carrier lifetimes ( τ ) under open-circuit conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further illustrate the impact of introducing the BDD unit on charge recombination, transient photovoltage (TPV) measurements were conducted. 65 As shown in Fig. S23 (ESI†), the TPV decay dynamics of the blend films can be used to extract the carrier lifetimes ( τ ) under open-circuit conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To carry out more comprehensive analysis, in addition to τ values, the corresponding carrier densities ( n ) can also be estimated using charge-extraction (CE) measurements performed at various illumination intensities in parallel. 65 Fig. S23 (ESI†) delineates that the n values vary with the light intensity, and the relationship between τ and n is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The utilization of solar photons in the NIR region has become increasingly important. [83] Using the low-band gap NFA IEICO-4Cl, we fabricated efficient semi-transparent OSCs with controllable colors (Figure 7a). [21] Yip et al [84] demonstrated that a heat-insulation function could be effectively integrated into semitransparent OSCs (Figure 7b).…”
Section: Multiple-function Integrationmentioning
confidence: 99%
“…Semitransparent photovoltaic cells should have high transmittance in the visible light range. The utilization of solar photons in the NIR region has become increasingly important [83] …”
Section: Further Development Of Single‐junction Oscsmentioning
confidence: 99%
“…Bulk heterojunction (BHJ) OSCs have attracted tremendous attention due to their various advantages, such as mechanical exibility, solution-processed capacity, light weight, and semitransparency. [1][2][3][4][5][6] In recent years, OSCs have undergone rapid progress due to the emergence of non-fullerene acceptors, e.g., ITIC, 7 IT-4F, 8 O-IDTBR, 9 PTIC, 10 and Y6. 11,12 Single-junction binary OSCs with Y6 and its derivatives as acceptors afford high PCEs of over 17%.…”
Section: Introductionmentioning
confidence: 99%